Comparison of aerobic and combined aerobic and whole-body vibration training effects on physical fitness in non-alcoholic fatty liver patients - (:unkn) unknown (WAGENINGEN ACADEMIC PUBLISHERS, 2021)
The aim of this study was to evaluate the effectiveness of exercises with whole-body vibration which was added to aerobic training on the physical fitness of patients with non-alcoholic fatty liver disease. Thirty-two patients diagnosed with non-alcoholic fatty liver (age 44.39 +/- 8.74 years) were randomly divided into an aerobic training + vibration group and an aerobic training + sham vibration group. The aerobic training was continued at 60-80% heart rate workload, 40 min per day during 3 days per week, for 8 weeks. Vibration were performed with dynamic and static exercises at 30 Hz, with a 2 mm amplitude, for 15 min. The energy expenditure responses were carried out by an exercise tolerance test system. Lower limb isometric muscle strength assessment was made with a calibrated handheld dynamometer from bilaterally knee extensors. The sit to stand test, and the time up and go test were used for physical performance evaluation. At eight weeks, both groups showed a significant reduction in the sit to stand (-1.62 +/- 1.00 vs -0.37 +/- 1.52), the time up and go test (-1.43 +/- 0.99 vs -1.39 +/- 1.06), the right lower extremity muscle strength (1.01 +/- 1.61 vs 1.22 +/- 2.82), and the energy expenditure scores (MET; 1.88 ml/kg/min, 95% confidence interval (CI) 1.19; 2.57, d=0.55, minimal clinically important difference (McID) = 0.69 vs 2.01 ml/kg/min, 95% CI 0.76; 3.24, d=0.26, McID = 1.54, respectively), however no significant differences emerged between groups (P >= 0.05). The addition of vibration exercises to an aerobic program did not provide additional benefits to physical fitness in patients with non-alcoholic fatty liver.
Keywords: fatty liver; aerobic exercise; acceleration; physical fitness; SKELETAL-MUSCLE; POSTMENOPAUSAL WOMEN; INSULIN SENSITIVITY; OLDER PERSONS; DISEASE; EXERCISE; STIFFNESS; STRENGTH; BENEFITS; BALANCE